Peran Indonesia Dalam Menangani Etnis Muslim Rohingya Di Myanmar - Rosyid, Mohammad (UI Scholars Hub, 2019)
Indonesia is a country that is independent but actively participates in global politics including in the case of state or majority oppression against minority ethnic or group, such as the case of Rohingya in Myanmar. Rohingya is a moslem minority ethnic living in Myanmar targeted in genocide and banished from the country under the military government. Meanwhile, the civil leader of Myanmar, Aung Sang Suu Kyi, remains silent despite her Peace Prize Nobel. On the other hand, the political stance of ASEAN needs to be strengthened to find the solution for Rohingya without intervening internal affairs of the country. Indonesia has supported Rohingya people both by delivering humanity aids, such as building school, hospital and providing basic needs, as well as persuading Myanmar government by means of diplomacy to protect Rohingya people. This kind of humanity acts should be maintained for the sake of human rights. Thus, Indonesia needs to ratify the Convention on Refugees of 1951.